Individual differences in scanpaths correspond with serotonin transporter genotype and behavioral phenotype in rhesus monkeys (Macaca mulatta) - Gibboni, Robert R.; Zimmerman, Prisca E.; Gothard, Katalin M. (Frontiers in Behavioral Neuroscience, 2009)
Scanpaths (the succession of fixations and saccades during spontaneous viewing) contain information about the image but also about the viewer. To determine the viewer-dependent factors in the scanpaths of monkeys, we trained three adult males (Macaca mulatta) to look for 3 s at images of conspecific facial expressions with either direct or averted gaze. The subjects showed significant differences on four basic scanpath parameters (number of fixations, fixation duration, saccade length, and total scanpath length) when viewing the same facial expression/gaze direction combinations. Furthermore, we found differences between monkeys in feature preference and in the temporal order in which features were visited on different facial expressions. Overall, the between-subject variability was larger than the within- subject variability, suggesting that scanpaths reflect individual preferences in allocating visual attention to various features in aggressive, neutral, and appeasing facial expressions. Individual scanpath characteristics were brought into register with the genotype for the serotonin transporter regulatory gene (5-HTTLPR) and with behavioral characteristics such as expression of anticipatory anxiety and impulsiveness/hesitation in approaching food in the presence of a potentially dangerous object.